Exploring the relationship between Islamic religious learning and community: Special reference to ‘Abdul Rahman Ibn Khaldun and Mohammad Tahir Ben Achour - Bensaid, Benaouda; Machouche, Salah (Emerald Group Publishing Limited, 2013)
Purpose – Muslims' commitment to religious learning and its institutions speaks of a genuine interest in a lifestyle characterized by education and wisdom, spiritual and religious well-being, in addition to sustainable intellectual and socio-cultural conditions of their communities. At the core of these critical contributions however, lays the question of the interplay between religious learning and community building, and the means according to which religious learning is continually the driving force for development and prosperity. This study aims to examine a number of questions pertaining to the character of Islamic religious learning while exploring the problems impeding religious learning from the effective development of the community. Specifically, this research draws on the perspectives of two prominent Muslim scholars, ‘Abdul Rahman Ibn Khaldun and Mohammad Tahir Ben Achour in an attempt to further understand the dilemmas impairing the position of Islamic religious learning in relation to the general context of Muslim communities. This inquiry opens new fields of critical inquiry on the role of religious learning today and brings to light some of the issues causing declining influence on the effective development of Muslim communities.